PENERAPAN MODEL PEMBELAJARAN TGT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII MTS ISLAMIYAH BELAWAN - Harahap, Risfa Rahma; Hasratuddin, Hasratuddin (Jurnal Abdi Insani, 2024)
This research was conducted because there were still relatively low mathematics learning outcomes of students, students were less enthusiastic about conventional learning methods and they did not understand the concepts in learning mathematics. Therefore, innovation is needed in learning methods that can improve students' understanding of concepts and interest in learning. One model that is considered effective is the TGT model which can facilitate a more interesting and enjoyable learning experience. This community service is to determine the increase in student learning outcomes after the TGT Cooperative Learning Model was implemented. In addition, to determine the classical completeness of student learning outcomes after being taught using the learning model. Community service was held at MTS Islamiyah Belawan in the even semester of 2023/2024. Classroom action research is a type of research that is carried out in five stages: class presentation, group learning, games, tournaments and team awards. The instruments used are tests and observations. The results of the research are that by using the TGT cooperative learning model, the average value of student learning outcomes increased to 68.16 in the first cycle and 84.5 in the second cycle. In cycle I, classical learning completion increased from 53.34% to 86.67% when the TGT learning model was applied. Of the 30 students who took the test, 26 (86.67%) of them met the completion criteria, namely achieving a score greater than or equal to 75, while 4 (13.33%) did not meet the completion requirements. During cycle II, the average point score for observing learning implementation activities in the classroom was 91.27 with the best group. So it is concluded that students have better learning outcomes with the TGT learning model. Furthermore, the completion of their learning outcomes is classified as complete.